Pathogenic variants in the TRIP11 gene cause a skeletal dysplasia spectrum from odontochondrodysplasia to achondrogenesis 1A. Issue 4 (5th January 2020) - Medina, Cristina T. N.; Sandoval, Renata; Oliveira, Gabriela; da Costa Silveira, Karina; Cavalcanti, Denise P.; Pogue, Robert
Abstract: The thyroid hormone receptor interactor 11 ( TRIP11 ) gene encodes the Golgi microtubule‐associated protein 210 (GMAP‐210), a protein essential for the operation of the Golgi apparatus. It is known that null mutations in TRIP11 disrupt Golgi function and cause a lethal skeletal dysplasia known as achondrogenesis type 1A (ACG1A), however recently, hypomorphic mutations in that gene have been linked to odontochondrodysplasia (ODCD), a nonlethal skeletal dysplasia characterized by skeletal changes in the spine and in the metaphyseal regions, associated with dentinogenesis imperfecta. Here we present two patients reflecting the phenotypic spectrum related to different TRIP11 variants. The first is a female child with ODCD, for whom a homozygous in‐frame splicing mutation in intron 9 of TRIP11 was identified. The mutation appears to lead to the expression of an alternative TRIP11 transcript, that may explain the less severe radiological alterations in ODCD. The second is a fetus with classical form of ACG1A, associated with typical molecular findings (frameshift) in exon 11 of TRIP11, both novel mutations. The two patients reported here represent the TRIP11 spectrum of skeletal dysplasia ranging from mild to lethal phenotypes, thereby enabling one to suggest a genotype–phenotype correlation in these diseases.